(untitled) (Research, Society and Development, 2021)
The aim of this study is to describe the caregivers and physical therapists’ perceptions of telehealth strategies in two cases of infants with Down syndrome during the COVID-19 pandemic in Brazil. Methodology: The physical therapy intervention program was carried out using synchronous and asynchronous methods according to the social context of each family. Results: The telehealth strategies were positively evaluated by caregivers and physical therapists. Conclusion: The study concluded that telehealth has promoted satisfactory results in infants’ physiotherapeutic monitoring, and it could be an additional tool for early intervention after the pandemic.